2019
DOI: 10.1016/j.ijhcs.2019.05.009
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of IJHCS and CHI: A quantitative analysis

Abstract: In this paper we focus on the International Journal of Human-Computer Studies (IJHCS) as a domain of analysis, to gain insights about its evolution in the past 50 years and what this evolution tells us about the research landscape associated with the journal. To this purpose we use techniques from the field of Science of Science and analyse the relevant scholarly data to identify a variety of phenomena, including significant geopolitical patterns, the key trends that emerge from a topic-centric analysis, and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…al. [57] identified an unequal global distribution of publications within both CHI and the International Journal of Human-Computer Studies. They concluded that "there are a number of countries that show a very high level of interest in what is happening in IJHCS and HCI but are unable to have a significant publishing presence or citation impact in these outlets."…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…al. [57] identified an unequal global distribution of publications within both CHI and the International Journal of Human-Computer Studies. They concluded that "there are a number of countries that show a very high level of interest in what is happening in IJHCS and HCI but are unable to have a significant publishing presence or citation impact in these outlets."…”
Section: Related Workmentioning
confidence: 99%
“…A factor contributing to this problem is that researchers in HCI are predominantly located in Western countries [5,57], which suggests that the majority of samples likely consist of Westerners. That the lack of geographic diversity in both authors and participants of published articles is a problem has been widely recognized in the behavioral sciences.…”
Section: Introductionmentioning
confidence: 99%
“…The human experts were given this spreadsheet and asked to classify each paper either with one of the five categories or with a "none of the above" tag. We then compared the seven annotation sets produced by the six human experts and by EDAM, considered as an additional annotator 29 . Table 2 shows the agreement between the annotators.…”
Section: Evaluation Of the Primary Study Classificationmentioning
confidence: 99%
“…Furthermore, AIDA can be used to train machine learning systems for predicting the impact of research dynamics [11]. A preliminary versions of AIDA was used to support a comprehensive analysis of the research trends in the main venues of Human-Computer Interaction [9].…”
Section: Introductionmentioning
confidence: 99%